Ni-Based Ohmic Contacts to n-Type 4H-SiC: The Formation Mechanism and Thermal Stability. (16th March 2016) - Kuchuk, A. V.; Borowicz, P.; Wzorek, M.; Borysiewicz, M.; Ratajczak, R.; Golaszewska, K.; Kaminska, E.; Kladko, V.; Piotrowska, A.
Abstract : The fabrication of low-resistance and thermal stable ohmic contacts is important for realization of reliable SiC devices. For the n -type SiC, Ni-based metallization is most commonly used for Schottky and ohmic contacts. Many experimental studies have been performed in order to understand the mechanism of ohmic contact formation and different models were proposed to explain the Schottky to ohmic transition for Ni/SiC contacts. In the present review, we summarize the last key results on the matter and post open questions concerning the unclear issues of ohmic contacts to n -type SiC. Analysis of the literature data and our own experimental observations have led to the conclusion that the annealing at high temperature leads to the preferential orientation of silicide at the heterointerface (0001)SiC//(013)δ -Ni2 Si. Moreover, we may conclude that only δ -Ni2 Si grains play a key role in determining electrical transport properties at the contact/SiC interface. Finally, we show that the diffusion barriers with free diffusion path microstructure can improve thermal stability of metal-SiC ohmic contacts for high-temperature electronics.